Factorial Invariance of the Scale Beliefs About Children’S Adjustment in Same-Sex Families in Spanish, Chilean, and Hispanic University Students - Barrientos-Delgado, J (SAGE Publications Inc., 2017)
This study examines the factorial invariance of the Scale on Beliefs About Children’s Adjustment in Same-Sex Families (SBCASSF) across countries in three samples: Chilean, Spanish, and Hispanic university students. The scale analyzes attitudes toward the consequences of the rearing and education of children by parents with a homosexual sexual orientation. The instrument consists of two subscales: Individual Opposition and Normative Opposition. The Spanish sample is composed of 199 university students, the Chilean sample is made up of 279 students, and the Hispanic sample consists of 114 students. The results provide empirical evidence for the reliability of the SBCASSF in the samples from the countries and its factorial invariance (strict invariance). Results are also provided about differences between countries and by sex. The SBCASSF could be a potentially useful measure for educators, psychologists, and other mental health professionals who wish to study beliefs about the child-rearing practices of same-sex parents. © The Author(s) 2017.